Effect of COVID-19 in Bangladesh: Challenge and Overcome - M. Shohel Rana; Mohammad Abu Tareq Rony; Nilufa Aktar; Kabir Hossain; Tonmoy Alam Shuvo; Susmita Begum; Asma Ul Hosna (Journal of Applied Science, Engineering, Technology, and Education, 2021)
To control and minimize, many countries have to try to impose radical lockdown, red zone and movement control or stay on their residents. The effectiveness of these alleviation measures is highly dependent on collaboration and the fulfillment of all members of a civilization. The knowledge, attitudes and practices people hold toward the disease play a vital role in determining a society’s willingness to accept behavioral change of the people. This study was to determine the Effect of COVID-19 in among the Bangladeshi public. A cross-sectional online survey of 260 Bangladeshi residents of various sectors and professions was conducted via Google form. Descriptive statistics, chi-square tests, t-tests and one-way analysis of variance (ANOVA) were conducted. Principal component analysis (PCA) was considered to design a standardized scale to measure the mental stress and socioeconomic crisis. Logistic regression was applied to estimate the statistically significant association between different variables on awareness level of the country and cluster analysis (CA) was applied to examine the reliability of each item according to the components to develop a composite score. The overall rate of the level of awareness of Bangladeshi people was only 25%, although 96.9% knowing COVID-19 epidemic. The 33.5% maintain lock down and 40.0% people maintain social distance. We found lack consciousness of People spreadCOVID-19that maybe increase about 68.1% over the country and there is positive correlation between people knowing COVID-19 and awareness level. Losses in education sector are found statistically significant. The PC 1 (first principal component) explained 9.328 % of the variance which was moderate positive loaded with locality people maintain social distance (0.568) and strong positive loaded with people maintain lockdown in locality (0.619). Moreover, result shows that, stay at home was the best method to reduce this pandemic situation, and agriculture sector may overcome this economic distress. However, Meta-Analysis showed that there is strong association between awareness levels of COVID-19 and washing hands daily in the lockdown area.